1998
DOI: 10.1108/00035599810198741
|View full text |Cite
|
Sign up to set email alerts
|

Relationship between the molecular structure and the inhibition performance of triazole compounds using electrochemical methods

Abstract: Corrosion inhibitors represent the most cost effective and flexible means of controlling internal corrosion associated with oil and gas production. Tests were carried out to demonstrate the structure/effect relationships which are effective in controlling the inhibition efficiency. To illustrate this approach, the substituent field effect at the paraposition of 1(Benzyl)1‐H‐4,5‐Dibenzoyl‐1,2,3‐ Triazole (BDBT) on corrosion inhibition has been investigated. Mild steel rotating cylinder electrode in acid media w… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
14
0

Year Published

2003
2003
2013
2013

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 26 publications
(15 citation statements)
references
References 11 publications
0
14
0
Order By: Relevance
“…In order to evaluate compounds as corrosion inhibitors and to design novel inhibitors, much more research works were concentrated on the studies of the relationship between structural characteristics of the organic compounds and their inhibiting effects [1][2][3][4][5]. It had been suggested that the most effective factors for the inhibiting effects are the electronegative atoms (such as, N, S, P, O, etc.)…”
Section: Introductionmentioning
confidence: 99%
“…In order to evaluate compounds as corrosion inhibitors and to design novel inhibitors, much more research works were concentrated on the studies of the relationship between structural characteristics of the organic compounds and their inhibiting effects [1][2][3][4][5]. It had been suggested that the most effective factors for the inhibiting effects are the electronegative atoms (such as, N, S, P, O, etc.)…”
Section: Introductionmentioning
confidence: 99%
“…9 Effect of the molecular structure of some quinones 1.361 C 6,3 -C 5, 4 1.340 C 7,14,2,5 -C 6,5,3, 13 1.484 C 11 -C 12 1.342 C-N 1.365 N-H 0.960 Table 2. Continued structure.…”
Section: Electron Densitymentioning
confidence: 99%
“…A considerable number of organic molecules were found to possess such corrosion inhibiting properties. In recent years attempts were made to correlate the protecting efficiency with the molecular structure of the inhibitor molecule [1][2][3][4][5][6][7][8][9][10][11][12]. The hope is, that a detailed knowledge of the effect of the chemical structure of a substance on its protective action would then allow to synthesize inhibitors with tailored properties.…”
Section: Introductionmentioning
confidence: 99%
“…Corrosion inhibitors are widely used in the control of carbon steel corrosion in the oil technology on the basis of its easy application, availability and economical cost [10]. Corrosion inhibitors are the cheapest and most flexible agent in the control of internal corrosion of long pipelines in the oilfields [6,11]. Tests of forty corrosion inhibitors added into oilfield brine have been described [12].…”
Section: Introductionmentioning
confidence: 99%